Frontispiece: Post‐Synthetic Decoupling of On‐Surface‐Synthesized Covalent Nanostructures from Ag(111). Issue 27 (22nd June 2016) - Rastgoo‐Lahrood, Atena; Björk, Jonas; Lischka, Matthias; Eichhorn, Johanna; Kloft, Stephan; Fritton, Massimo; Strunskus, Thomas; Samanta, Debabrata; Schmittel, Michael; Heckl, Wolfgang M.; Lackinger, Markus
Abstract : On‐Surface Synthesis M. Lackinger and co‐workers show in their Communication onpage 7650 ff. that iodine intercalation enables the post‐synthetic decoupling of on‐surface‐synthesized covalent organic nanostructures from Ag(111).